Wahdatul ‘Ulum Perspective Systemic Thinking: Study Integration of Science in Islamic Education - Zulkipli Nasution; Selamat Pasaribu; Surianto Surianto; Ahmad Ridwan; Hasan Bakti Nasution (AL-ISHLAH: Jurnal Pendidikan, 2023)
Systemic thinking ability is a basic potential for humans in life. This study aims to analyze the study of systemic thinking from Wahdatul 'Ulûm's perspective as a study of the integration of knowledge in Islamic education. The approach to this research is a qualitative type, with a literature study method. Sources of data and study analysis materials used scientific literature obtained from credible websites, including Google Scholar, SINTA, Science Direct, and DOAJ. The results of this study indicate that (1) the ability to think thinking is a form of optimization of the potential possessed by humans and nature as "perfect beings" created by Allah swt. Islam teaches many systemic and critical thinking terms, such as al-tafakkur, al-tadzakkur, al-tadabbur, al-tandzur, and al-ta'aqqul. This potential supports the task of humanity as caliph fil ardh and 'abd on earth; and (2) Systemic thinking is relevant to the Wahdatul 'Ulm paradigm as a form of integrality (unity) of science, views that science is integral, interconnected, and holistic which is embodied in the form of vertical, horizontal, actuality, ethical, and intrapersonal integration. Human potential to have the ability to think systematically and critically is in line with the application of Wahdatul 'Ulm which eliminates all forms of scientific dichotomy, with the paradigm that everything comes from a single entity that is inseparable, interconnected and contains wisdom.